On stable finiteness of group rings - Dykema, K.; Juschenko, K. (Algebra and Discrete Mathematics, 2015)
For an arbitrary field or division ring K and an arbitrary group G, stable finiteness of K[G] is equivalent to direct finiteness of K[G×H] for all finite groups H.